CONDITIONS OF ARCHITECTURAL ACCESSIBILITY OF BUILDINGS OF BASIC HEALTH UNITS IN LINE WITH CURRENT STANDARDS: ARE THERE ADVANCES? - Carlos Pereira de Jesus, Ely; Gonçalves Barbosa, Tayna; Mesquita Antunes, Felipe; Cristina Ferreira Silva, Maria; de Oliveira Duarte, Nayra; Diniz Rabelo Lopes, Vanusa; Alencar Fróes, Karine; de Jesus Santos Bandeira, Leandro; Helena Heineck, Lúcia; Dourado Souza, Fabiana; Santos Félix, Matheus; Gonçalves de Amorim, Aline; et al. (Health and Society, 2026)
The objective of this study was to reflect on the conditions of architectural accessibility of buildings in Basic Health Units in accordance with NBR 9050/2015. A theoretical-reflective study was conducted based on the precepts of continuing education and reflective training in health. The search was conducted in the second half of 2024 through the guiding question. Access to health services in the Family Health Strategy is considered one of the greatest difficulties regarding the assistance provided to the population. According to data from the World Health Organization, the physically disabled face great obstacles to transport themselves to the ESF, starting with the simple act of leaving home, thus finding places that are not conducive to receiving them without some difficulty. The evaluation of accessibility in the Family Health Strategy aims to observe for future discussions about the difficulties encountered by the physically disabled. It is concluded that the conditions of architectural accessibility of buildings of basic health units in accordance with the legislation were commonly limited to the letter of the law.